Analisis Pemahaman Konsep Siswa SMAN 11 Medan dan SMAS Imelda Medan pada Materi Fluida Statis - Ramadani, Naillah Putri (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2024)
This research was conducted to analyze the conceptual understanding of high school students in two schools, namely SMA Negeri 11 Medan and SMA Swasta Imelda Medan on static fluid material. The method used is descriptive analysis. Data was taken from each school as many as 10 students in class XI. The instrument consists of 10 test questions in the form of multiple choices. The results of the analysis show that students' conceptual understanding of static fluid material at SMA Negeri 11 Medan is classified as sufficient with an average score of 47, while at SMA Private Imelda Medan is classified as sufficient with an average score of 52. At SMA Negeri 11 Medan students have difficulties in discussion of the definition of static fluid and discussion of buoyant force in Archimedes' law and at Imelda Medan Private High School students have difficulty discussing buoyant force in the context of static fluid.